Effects of high volume upper extremity plyometric training on throwing velocity and functional strength ratios of the shoulder rotatores in collegiate baseball players - Carter, A. B.; Kaminski, T. W.; Douex, A. T.; Knight, C. A.; Richards, J. G. (The Journal of Strength and Conditioning Research, 2007)
To achieve maximal force output, clinicians and coaches have been experimenting with upper extremity plyometric exercises for years, without sufficient scientific validation of this training method. The goal of this study was to examine the effects of an 8-week course of high volume upper extremity plyometric training on the isokinetic strength and throwing velocity of a group of intercollegiate baseball players. Twenty-four Division I collegiate baseball players (age: 19.7 +/- 1.3 years; height: 183.9 +/- 5.9 cm; mass: 90.7 +/- 10.5 kg) were recruited to participate in this study. Throwing velocity, isokinetic peak torque, isokinetic functional strength ratios, and time to peak torque were measured pre- and posttraining. Subjects were rank-ordered according to concentric internal rotation (IR) strength and were assigned randomly to either the plyometric training group (PLY) or the control group (CON). Training consisted of 6 upper extremity plyometric exercises ("Ballistic Six") performed twice per week for 8 weeks. Subjects assigned to CON performed regular off-season strength and conditioning activities, but did not perform plyometric activities. PLY demonstrated significant increases (p < 0.05) in throwing velocity following 8 weeks of training when compared with CON (83.15 mph [pre] vs. 85.15 mph [post]). There were no statistically significant differences in any of the isokinetic strength measurements between PLY and CON groups pre-to posttraining. Statistically significant differences were seen within PLY for concentric IR and eccentric external rotation (ER) isokinetic strength at 180°/s and 300°/s; and within CON for eccentric ER isokinetic strength at 300°/s and concentric IR isokinetic strength at 180°/s. The Ballistic Six training protocol can be a beneficial supplement to a baseball athlete's off-season conditioning by improving functional performance and strengthening the rotator cuff musculature.